Impacts of environmental policy uncertainty on urban environmental pollutant emissions in China: a study based on textual analysis - Li, Rongda; He, Jing (Frontiers in Environmental Science, 2023)
How to accelerate the clean use of fossil energy and promote the transformation and upgrading of energy structure is an important challenge commonly faced by countries around the world. In the post-Covid-19 era, the uncertainties faced by countries around the world are increasing and the frequency of policy adjustments in various countries is accelerating. The discharge of pollution by enterprises is significantly impacted by environmental regulatory policies. Under the carbon neutrality goal, the uncertainty of environmental policy caused by multiple political factors can directly influence the decisions made by businesses and residents, in turn, affect their confidence and expectations. However, researchers have given limited attention to measuring the environmental policy uncertainty index (EPUI). In this paper, we select 460 newspapers from the China National Knowledge Infrastructure (CNKI) newspaper database from 2001 to 2016 and use the text analysis method to directly construct China's national, provincial, and prefecture-level EPUI. The results show that China's EPUI has obvious stage characteristics and regional characteristics. By applying the Chinese city-level EPUI to the field of urban pollution reduction, we have obtained an important finding that when urban environmental policy uncertainty increases by 1%, urban industrial sulfur dioxide emission decreases by about 0.145%, and carbon dioxide emission decreases by about 0.053%. We believe that this is due to an increase in environmental policy uncertainty inhibiting the development and scaling of secondary industries.